EXPLORING THE PHENOMENON OF OBESITY AMONG TEENAGERS: CULTURAL PERCEPTIONS, CAUSES, AND PREVENTIVE SOLUTIONS - Aryanti , Novina (Universitas Pesantren Tinggi Darul Ulum, 2025)
Adolescent obesity is a growing concern in Surabaya, influenced by multiple interconnected factors such as unhealthy eating habits, lack of physical activity, limited nutritional knowledge, family behaviors, peer pressure, and media exposure. This study identifies these factors and examines their impact on adolescent obesity, supported by the energy balance theory and behavioral epidemiology. Findings indicate that family routines and cultural perceptions of food play significant roles in shaping adolescents’ eating behaviors. The study also highlights how peer influence and the portrayal of food and body image in social media contribute to unhealthy lifestyle choices. Solutions proposed include the integration of nutrition education in schools, promotion of fun and social physical activities, and stronger family involvement in monitoring eating habits. Furthermore, school policies should support healthy food choices, and healthcare professionals should provide regular guidance and counseling. A collaborative approach involving schools, families, and health professionals is essential for long-term behavior change. This research emphasizes the need for community-wide efforts to create an environment that promotes healthier lifestyles and aligns with local cultural values. Keywords: Adolescent obesity,Teenagers, Cultural perceptions